Review Response Strategy, Online Reputation, and Consumer Trust: A Moderated Mediation Model of Marketing Performance in the Hotel Industry of Medan City - Demak Claudia Yosephine Simanjuntak; Darwin Lie; Sofiyan Sofiyan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines how Review Response Strategy and Online Reputation shape Marketing Performance, positioning Consumer Trust as a mediating variable and Service Quality as a moderator, within the hospitality sector of Medan City, Indonesia. A quantitative paradigm was adopted, employing Partial Least Squares Structural Equation Modeling (PLS-SEM) applied to data gathered from 130 respondents comprising hotel guests and frontline management staff. The results confirm that both independent variables—Review Response Strategy and Online Reputation—exert significant positive effects on Consumer Trust, which subsequently drives Marketing Performance. Consumer Trust functions as a partial mediator in the pathway from Online Reputation to Marketing Performance. Additionally, Service Quality strengthens the Consumer Trust–Marketing Performance relationship, whereby hotels delivering higher service standards derive greater trust-driven performance gains. An Adjusted R² of 0.720 attests to the model’s robust explanatory capacity. The findings carry actionable implications for hospitality operators in Medan seeking to harness digital review management as a strategic marketing lever.